1982
DOI: 10.1111/j.1365-2621.1982.tb10119.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Four Anticaking Agents on the Bulk Characteristics of Ground Sugar

Abstract: Powdered sugars are known to be fairIy cohesive mater-I Fine silicon oxide, sodium aluminum silcate, tricalcium phosphate and calcium stearate powders were admixed with dry ground sugar at four concentration levels between 0.1 to 2%. Appreciable increase in loose -bulk density and decrease in compressibility were notice able at 0.1% concentration in alI four agents. Theeffect reached an apparent peak'or a flat maximum at an agent concentration of about OS-l%. With the exception of silicon oxide treated powders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 12 publications
1
17
0
1
Order By: Relevance
“…This fact illustrated that these additives acted as flow agent or solid lubricant which could result in the slippage of raw materials leading to a decrease in feed rate. The effect of lubrication was also observed in previous powder industry studies, an appropriate level of flow agent addition could improve the flowability of the powder except an excessive level could prevent (Hollenbach, Peleg, & Rufner, 1982;Peleg & Hollenbach, 1984;Peleg, Mannheim, & Passy, 1973).…”
Section: Resultssupporting
confidence: 60%
“…This fact illustrated that these additives acted as flow agent or solid lubricant which could result in the slippage of raw materials leading to a decrease in feed rate. The effect of lubrication was also observed in previous powder industry studies, an appropriate level of flow agent addition could improve the flowability of the powder except an excessive level could prevent (Hollenbach, Peleg, & Rufner, 1982;Peleg & Hollenbach, 1984;Peleg, Mannheim, & Passy, 1973).…”
Section: Resultssupporting
confidence: 60%
“…In previous powder industry studies, it was also observed that an appropriate level of flow agent addition could improve the flowability of powder but an excess level could prevent it (Hollenbach, Peleg, & Rufner, 1982;Peleg & Hollenbach, 1984;Peleg, Mannheim, & Passy, 1973). Therefore, the addition of excess eggshell powder decreased the effect of lubrication resulting in less decrease in feed rate leading to inverse changes in feed rate.…”
Section: Resultsmentioning
confidence: 99%
“…Above a certain inclusion rate, however, the conditioner can retard the overall flow of the material (Hollenbach et al, 1982;Nash et al, 1965;Irani et al, 1959). If the surface affinity between the host powder and conditioner is strong, then large effects will be present in the bulk density and compressibility at inclusion concentrations of 0.1 to 0.5%.…”
Section: Flow Conditioners and Anticaking Agentsmentioning
confidence: 99%
“…If the blends of the conditioning agents result in the filling of interparticle void space only, then the conditioner's bulk density is given by (Hollenbach et al, 1982):…”
Section: Bulk Densitymentioning
confidence: 99%